Symbolization : representation and communication - Rose, James, 1946- (Psychoanalytic ideas., 2007)
Because psychoanalysis is a science of subjectivity, it is no surprise that symbolism has been of central interest from its inception and early development. There are few phenomena more obviously subjective than symbols. They conjure a particular fascination because of their enigmatic quality. For this reason, they manage to communicate something in an obscure manner. Thus, they partly hide. This duality and ambiguity approaches the fleeting and evanescent quality of subjectivity itself: at its most subjective. This book is assembled in such a way that the reader can trace the development of t.